2016
DOI: 10.1038/jhh.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

Race/ethnicity determines the relationships between oxidative stress markers and blood pressure in individuals with high cardiovascular disease risk

Abstract: Oxidative stress (OS) and cardiovascular (CV) reactivity are related to CV morbidity and mortality. However, little is known about the relationships between these CV risk factors and their confounders. We hypothesize that higher OS is linked to higher blood pressure (BP) reactivity to acute laboratory stressors and in the natural setting. We studied 137 subjects with a family history of hypertension and early myocardial infarction. There were 63 European Americans (EA’s) (38 males) and 74 African Americans (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Observations from our cohort of CKD patients linked BP variability with a prevalence of sleep disorders such as obstructive sleep apnea, insomnia and restless leg syndrome further supporting the hypothesis that endothelial dysfunction and glomerular damage play a crucial role in the development of BP variation and in worsen disease progression in these patients [40][41][42]. Evidences for the correlation of oxidative stress and BP variability can be observed in population at high cardiovascular risk such as subjects with familial history of essential hypertension and myocardial infarction and type 2 diabetes mellitus and hypertension where BP variations significantly correlate with 8-hydroxydeoxyguanosine, 8-isoprostane and diacron-reactive oxygen metabolites respectively [43,44].…”
Section: Oxidative Stress Damage In Ckd and Kidney Failure With Or Without Replacement Therapy Patientssupporting
confidence: 54%
“…Observations from our cohort of CKD patients linked BP variability with a prevalence of sleep disorders such as obstructive sleep apnea, insomnia and restless leg syndrome further supporting the hypothesis that endothelial dysfunction and glomerular damage play a crucial role in the development of BP variation and in worsen disease progression in these patients [40][41][42]. Evidences for the correlation of oxidative stress and BP variability can be observed in population at high cardiovascular risk such as subjects with familial history of essential hypertension and myocardial infarction and type 2 diabetes mellitus and hypertension where BP variations significantly correlate with 8-hydroxydeoxyguanosine, 8-isoprostane and diacron-reactive oxygen metabolites respectively [43,44].…”
Section: Oxidative Stress Damage In Ckd and Kidney Failure With Or Without Replacement Therapy Patientssupporting
confidence: 54%
“…This research is subject to several limitations. First, our findings are not generalizable outside of populations of CAD patients (119, 120). .…”
Section: Discussionmentioning
confidence: 62%
“…This is typical of the racial distribution of Georgia, but not many other areas of the country. Although AAs have an increase in hypertension (119) and oxidative stress (120), studies have not shown an increase in stress-induced blood pressure reactivity (120). Therefore the impact on race in this group is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These two diseases affect a large segment of population in the world with 422 million for the diabetes [WHO (World Health Organization), 2016] and 9.4 million deaths worldwide every year for hypertension (Lim et al, 2012). Diabetes mellitus and hypertension were enhanced oxidative stress and changes antioxidant capacity (Yang et al, 2011;Kapuku et al, 2016). Several reports had shown that the chronic administration of ouabain to Wistar rats induces hypertension (You et al, 2014;Davel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%